National Identities and Socio-Economic Development in European Union - Cezar Teclean (CES Working Papers, 2018)
This paper analyses the relationship between identity and level of socio-economic development in the member states of the European Union. This work is an empirical study which uses original data on the number of national mottos and country logos, GDP/ Capita and Human Development Index (HDI) for 2016 disaggregated by states of the EU28. Our findings suggest the existence of a symmetrical interdependence between the consistency of national identities and the degree of socio-economic development, between which there is a relative territorial overlap. We attempt to demonstrate that the symmetry of their arrangement with each other maps out a community-wide asymmetry, resulting in a territorial cohesion deficit and segregated segregation of the Union, generating an asymmetric European Union with more identity-development speeds.
Keywords: O52; O57; 330; national identities; development; identity indicators; national motto; country logo